1992
DOI: 10.1093/ije/21.5.966
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Self-Reported Physical Activity in Latinos

Abstract: The reliability and validity of six self-report physical activity measures were assessed in Latino adults. Validity was assessed by caltrac activity monitors, 'significant others', and construct analyses. Vigorous activity measures had higher reliability and validity (e.g. r > 0.40, P < 0.05) than moderate intensity measures. Though measures varied in their validity, the use of standard physical activity measures with Latinos was supported, and recommendations for specific measures were provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 0 publications
1
65
0
1
Order By: Relevance
“…Cards that listed examples of moderate, hard, and very hard activities were used during the interview to help participants with the classification of their activities and included examples of home, occupational, and sports/recreational activities at each intensity level. These examples are consistent with the materials utilized in the original PAR interview and have good reliability and validity in Latino adults (Rauh et al, 1992).…”
Section: Methodssupporting
confidence: 72%
“…Cards that listed examples of moderate, hard, and very hard activities were used during the interview to help participants with the classification of their activities and included examples of home, occupational, and sports/recreational activities at each intensity level. These examples are consistent with the materials utilized in the original PAR interview and have good reliability and validity in Latino adults (Rauh et al, 1992).…”
Section: Methodssupporting
confidence: 72%
“…[23][24][25] In addition, the validity of self-report could vary according to race/ethnicity, language, education, and health status. [26][27][28] The validity of the HRS physical activity questions has not been assessed by comparison to direct measurement of physical activity. However, the LTPA questions are similar to questions used in other validated measures.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, other studies have shown that the SAPAC tool is a reliable metric of physical activity in Latino adults. 30 And because children tend to overreport physical activity, consistent with tool developer recommendations, we used the SAPAC as a relative measure of activity rather than an absolute measure.…”
Section: Limitationsmentioning
confidence: 99%